New star [large type] - Christian, Lana (Christian, Lana. Magi's Encounters, 2025)
"Akilah, a highly respected priest-scholar in Magi society, considers all his astronomy discoveries well-deserved stepping-stones to a more fulfilling life. But the appearance of a new star in the sky challenges his priorities. As Persia totters on the brink of an undesirable king coming to power, Akilah declines a position that could turn that tide. Instead, he studies a star that doesn't appear in any almanac or religious writings. Except perhaps Jewish. When he and his colleagues uncover a few Jewish prophecies linking the star to an eternal king, Akilah becomes the target of Persia's religious and governmental conflicts. Jailed for crimes he didn't commit, Akilah must rely on questionable resources to free himself and reach Jerusalem. Persia's purists aren't the only ones bent on keeping their country free of Jewish influences. Akilah realizes his knowledge of Jesus could potentially destroy Magi society and its power over Persia's official religion and government. Untrusting of his Council, a thousand miles from aid, and bound in a potentially career-ending contract, Akilah must decide how far he will go to protect what he knows of Jesus and whether the cost of his belief is worth the risk."--